Household CH4 and N2O Footprints of Major Economies - Caihui Yan (American Geophysical Union (AGU), 2021)
Abstract Reducing CH4 and N2O emissions plays an essential role in tackling global warming. Most previous studies focused on the direct CH4 and N2O emissions of an economy, while ignoring the CH4 and N2O emissions induced by household consumption in the final consumption of an economy. This study analyzed household CH4 and N2O footprints of the major economies and identified the decoupling and inequality of household CH4 and N2O emissions based on the multi‐regional input‐output analysis and structural path analysis from 1995 to 2014. Results demonstrated that global household CH4 and N2O emissions increased by 8.4% in 2014 compared to 1995. Developing economies such as China, Brazil, India, and Indonesia witnessed a rapid growth of household CH4 and N2O emissions, but the opposite could be observed in developed economies such as Germany, Japan, the UK, and the US. A large amount of CH4 and N2O emissions related to household consumption were transferred from developed economies to developing economies. In terms of the relationship between economic development and household CH4 and N2O emissions, the US, the UK, and Japan showed a strong decoupling status in 2014, while China and Indonesia showed a weak decoupling status. Meanwhile, the household emission inequality in developing economies was higher than that in developed economies. By exploring the relationship between economy and household CH4 and N2O emissions, it is helpful to assist developed and developing economies to adopt household CH4 and N2O emission reduction policies in line with their economic development stages.